Penanaman Nilai Sopan Santun pada Tahap Moral Loving/Moral Feeling melalui Mata Pelajaran Tahfidz Al-Qur'an - Yulianti, Vira; Muliati, Indah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Manners are one form of Indonesian culture that is important to be preserved and upheld because it is an important element in socializing with others. This study aims to find out how teachers communicate students' feelings of love and need (moral loving/moral feeling) on the value of manners in the Qur'anic Tahfidz subject. This research uses qualitative methods with a case study approach. Data sources were taken from five informants through in-depth interviews selected using purposive sampling techniques. The five informants included two Qur'anic Tahfidz teachers, one school principal and two students. To obtain research data, researchers use a set of interview guidelines and observation guidelines as research instruments. Data collection techniques used in this study are observation, interviews and documentation. While the data analysis techniques used are data collection, data reduction, data presentation and conclusions. The results showed that there are two ways teachers instill Moral Loving/Moral Feeling for students for the value of manners, namely by setting an example and telling stories. The example in question is an example of behavior given by teachers through their daily behavior that must reflect the value of manners, both in terms of dressing, speaking, and behaving towards others. Meanwhile, the giving of stories is carried out by teachers by conveying Islamic stories in the time of the Prophet and Apostles that can motivate students so that there will be a sense of love and desire to be polite towards others.